Air and Water‐Stable n‐Type Doping and Encapsulation of Flexible MoS2 Devices with SU8. (8th November 2018) - Kung, Yen‐Cheng; Hosseini, Nahid; Dumcenco, Dumitru; Fantner, Georg E.; Kis, Andras
Abstract: Favorable mechanical and electrical properties motivate the use of 2D semiconductors in flexible electronic devices. One of the main challenges here is the absence of a practical doping strategy which should provide air‐stable, tunable doping levels in a process with a low thermal budget. Here, it is shown that SU8, an epoxy‐based photoresist, can be used for nondegenerate n‐type doping of monolayer MoS2 . The doping level can be finely tuned via low‐temperature annealing. The doping method exhibits good ambient stability. The high degree of mechanical flexibility and low processing temperature also allows the integration of SU8 coating with flexible MoS2 FETs, where it can provide both controllable doping and act as an encapsulation layer. The demonstrated stability of the devices to bending and exposure to water confirms the attractiveness of using SU8 in flexible electronic devices based on 2D semiconductors in a simple, versatile and scalable approach. Abstract : It is shown that the photoresist SU8 can be used for n‐type doping of monolayer MoS2 with good ambient stability. The doping level can easily be controlled during processing by changing the resist baking time. In addition to doping, the SU8 layer can also act as an encapsulation layer and protect flexible MoS2 transistors from direct submersion in water.